Overexpression of OsPIL1 enhanced biomass yield and saccharification efficiency in switchgrass. (November 2018) - Yan, Jianping; Liu, Yanrong; Wang, Kexin; Li, Dayong; Hu, Qingquan; Zhang, Wanjun
Highlights: Overexpression of OsPIL1 gene in switchgrass improved biomass yield and saccharification efficiency of OsPIL1 transgenic switchgrass plant. The higher expression level of OsPIL1 co-related to taller plant height and longer epidermal cell of transgenic plant. The results suggested that the OsPIL1 can be used as a useful molecular tool in improving plant biomass with the purpose of plant fiber biofuel ethanol production. Abstract: Switchgrass ( Panicum virgatum L.) is a herbaceous cellulosic biofuel plant with broad adaptability. However, the intrinsic recalcitrance of biomass and limited land for switchgrass planting hinder its utilization as feedstock for biofuel ethanol production. The OsPIL1 ( PHYTOCHROME INTERACTING FACTOR 3-LIKE 1 ) gene encodes a basic helix-loop-helix transcription factor. Its expression is induced by light, which facilitated the expression of cell wall-related genes, promoted cell elongation and resulted in longer internode in rice. Here, we introduced the OsPIL1 gene into switchgrass by Agrobacterium -mediated transformation with the aim of improving biomass yield of transgenic switchgrass plants. The transgenic plants were verified by PCR, Southern-blotting, RT-PCR and qRT-PCR tests, respectively. The transgenic plants overexpression of OsPIL1 showed increased plant height and biomass yield. Microscopy analysis showed that the length of epidermal cells of transgenic plants was longer than that of wild type. OsPIL1 overexpressed transgenic switchgrass plants also released more soluble sugar after enzymatic hydrolysis, indicating improved saccharification efficiency. The results suggest OsPIL1 can be used as a useful molecular tool in improving plant biomass and saccharification efficiency with the purpose of plant fiber biofuel ethanol production.